Data Mining in Grouping Indihome Customer Data Using the K–Means Clustering Method at PT.Telkom Akses - Egi Affandi; Syahrin Syam Noor Berutu; Yohanni Syahra; A. Amrullah (Institute of Computer Science (IOCS), 2021)
PT. Telkom Akses is part of the PT. Telekomunikasi Indonesia, Tbk (Telkom) company whose shares the stock and fully owned by Telkom.Telkom is a state owned company and as an IndiHome service Provider. So far, PT. Telkom Akses still has problems in classifying customer data. Based on these problems, PTTA requires a computer application that can cluster customer data and use data mining that can help solve problems that occur using the clustering method.. One of the methods offered to solve this problem is the k-means algorithm. The results of this study, the authors design and design a desktop-based information system that can implement the clustering method to produce customer data clusters according to the needs of PT. Telkom Access